2021
DOI: 10.5213/inj.2142042.021
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Aging and the Lower Urinary Tract: The Future of Urology

Abstract: Lower urinary tract symptoms (LUTS) are common among elderly people, with significant effects on individuals, caregivers, and the wider health care system. As the elderly population with multiple comorbidities is increasing, the burden of LUTS will increase. This review describes the demographic trends in the aging society, changes in lower urinary tract function with aging, and deterioration of physical and cognitive function in aging, as well as what has been done regarding geriatric urology and what urologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…The relationship between LUTS and frailty remains unknown because crosssectional studies can only address association. 5,7 Frailty alters the level of physical activity, which may contribute to LUTS. On the other hand, LUTS may affect frailty via frequent voiding, especially at night.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between LUTS and frailty remains unknown because crosssectional studies can only address association. 5,7 Frailty alters the level of physical activity, which may contribute to LUTS. On the other hand, LUTS may affect frailty via frequent voiding, especially at night.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they are components of heterogeneous syndromes. The relationship between LUTS and frailty remains unknown because cross‐sectional studies can only address association 5,7 . Frailty alters the level of physical activity, which may contribute to LUTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main drug therapies for OAB include anti‐cholinergic agents, β3‐adrenoceptor agonist, and combination therapies of those drugs 19 . However, an association between anti‐cholinergic agents and an increased risk of falls and cognitive, physical, and functional impairment has been reported 20 ; thus, anti‐cholinergic burden has to be considered in OAB treatment among the older adult population. A network meta‐analysis regarding the safety and efficacy of treatments for OAB among elderly showed that the β3‐adrenoceptor agonist was similarly effective to anti‐cholinergic agents and did not cause adverse events that were typically associated with anti‐cholinergic agents 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Lower urinary tract symptoms (LUTS) such as incontinence and bladder storage or voiding issues are more likely to occur in females than males. It has been estimated that up to 80% of women experience LUTS 15 . However, the frequency of symptoms and their impact on women's wellbeing varies from mild to more severe.…”
Section: Discussionmentioning
confidence: 99%